Synthesis and properties of amphiphilic star block copolymers with star macroinitiators based on a one‐pot approach. Issue 12 (25th April 2013) - Jiang, Xiubo; Hu, Lin; Chen, Yongming
Abstract : Amphiphilic star block copolymers were obtained using polystyrene star macroinitiators prepared by a two‐step temperature‐controlled process in one pot. Abstract: Previously, star polystyrenes (PSs) have been prepared by atom transfer radical polymerization (ATRP) of N ‐[2‐(2‐bromoisobutyryloxy)ethyl]maleimide (BiBEMI) with a large excess of styrene (St) in one pot. But linear PSs were also present during the formation of the star polymers. In the work reported here, we found that control of the formation of star polymers using a one‐pot approach can be improved by using a two‐step process. The polymerization was conducted first at a low temperature to form multifunctional cores by copolymerization of BiBEMI and St. Second, on increasing the temperature, homopolymerization of St occurred to grow PS arms. Then a series of amphiphilic star polystyrene‐ block ‐poly(acrylic acid)s, (S14 A x )16, were prepared by ATRP of tert ‐butyl acrylate with the star PSs as macroinitiators, followed by selective acidolysis of the poly( tert ‐butyl acrylate) blocks. Their micellization was studied using dynamic light scattering, which suggested that (S14 A112 )16 amphiphilic star block copolymers could form unimolecular micelles in a basic aqueous solution. Then pyrene molecules were encapsulated using the (S14 A112 )16 amphiphilic star copolymers and the loading capacity was investigated with UV and fluorescence spectroscopy. © 2013 Society of Chemical Industry